Peran Efektivitas Sistem Informasi dalam Memperkuat Tata Kelola Keuangan pada Instansi Pemerintah - Ari Hadi Prasetyo; Iwan Darmawansyah; Nurlela Nurlela (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Digital transformation in the public sector requires financial information systems to not only function administratively, but also to strengthen transparency, accountability, and control. In practice, these benefits do not always materialise if the system is not effective for users, thus requiring empirical studies to assess its role in financial governance. This study aims to analyse the effect of Information System Effectiveness on Financial Governance in public sector financial management agencies in Indonesia. The research uses a quantitative approach with an explanatory type and a cross-sectional survey design. The research population consists of all employees involved in financial management and using financial information systems in the agencies studied. The sampling technique uses purposive sampling with the criteria of active users of financial information systems, resulting in a sample of 120 respondents. Data were collected through a Likert scale questionnaire and analysed using PLS SEM with the help of SmartPLS through measurement model and structural model evaluation. The results show that information system effectiveness plays a role in strengthening financial governance because it supports the availability of more accurate, consistent, and timely information, thereby improving the orderliness of financial reporting, supervision, and control. The implications of this study emphasise the importance of improving information quality, system integration, and user training support in order to strengthen and sustain financial governance.